PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL MELALUI KEMAMPUAN INTERPERSONAL PEMIMPIN BERBASIS SYARIAH (STUDI KASUS PADA BMT DI KOTA PEKALONGAN) - Gunawan Aji; Nur Kholili (Jurnal Hukum Islam, 2014)
This research examines the effect of budget participation on managerial performance by using regression analysis. The research also reviews contingency theory to view the fit between budget participation, leaderhip style of Islamic and managerial performance using residual approach. The application of residual analysis is used to examine the interaction of fit between budget participation and Islamic leadership style an its impact on managerial performance. The application of this approach is expected to encourage the potency of “fit: and informative omdel forming in the contingency theory of management accounting in the future.Based on respon 38 manager of BMT in Pekalongan, the results of research shows that budgetary participation has no direct effect on managerial performance. As well as the leadership style of Islamic (sharia-based leader interpersonal skills) does not affect the relationship between budgetary participation and managerial performance.